Recent development on the uses of alternative fuels in cement manufacturing process. (1st April 2015) - Rahman, Azad; Rasul, M.G.; Khan, M.M.K.; Sharma, S.
Abstract: Cement manufacturing is one of the leading energy consuming and heavy pollutant processes which is accountable for CO2, NOX, SO2 emissions and some heavy metal discharge from the pre-calciner kiln system. In past few decades there has been an enormous amount of researches to reduce the energy and environmental cost by using alternative fuel and raw material. In recent years utilisation of alternative fuels in cement manufacturing has gained a wide attention due to its effectiveness in substituting the thermal energy requirement from fossil fuels and reducing the pollutant emission. Alkaline environment, high temperature and long residence time allow rotary kiln to burn a wide range of waste and hazardous material. Recent development on the usage of alternative fuels in cement industry is presented in this paper and many of the research articles relevant to this study is reviewed and discussed. Studies on the impact of alternative fuels on environmental emission have also been included in this review. This paper provides a thorough understanding and status of alternative fuels and their usage in cement industry and highlights their positive impact on environment. This study offers a guideline for planning and implementing alternative fuel usage in cement industry around the world, particularly in Australia. The paper revealed that meat and bone meal (MBM) could be the best alternative fuel option for Australia with a substitution rate of 40%.